Comparación de la eficacia de dos desinfectantes sobre microorganismos frecuentes en superficies en contacto con alimentos - Vásquez Chumbe, Jessy Patricia (2025)
Conventional chemical disinfectants, although effective, are toxic to people and the environment, and their continuous use can promote the emergence of microbial resistance. In this context, the formulation of disinfectants from plant extracts and essential oils, taking advantage of Amazonian biodiversity, emerges as a promising alternative. This study evaluated the ethanolic extract of Chamaesyce thymifolia (L.) Millsp. as a natural disinfectant against bacteria, comparing its efficacy with sodium hypochlorite on food-contact surfaces. Preliminary antibacterial activity was assessed by disk diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) against 8 bacterial strains at different concentrations. The disinfectant efficacy of the extract and sodium hypochlorite was evaluated using quantitative suspension tests (dilution-neutralization) and non-porous surface tests (stainless steel), at various concentrations, contact times, conditions (dirty and clean), and at room working temperature against Staphylococcus aureus and Enterococcus hirae. Disk diffusion results showed sensitive and moderate susceptibility for Salmonella Typhimurium, Staphylococcus aureus, Escherichia coli, Enterococcus faecalis, and Enterococcus hirae. The MIC demonstrated moderate activity, and MBC values of 4 and 8 mg/mL for Staphylococcus aureus and Enterococcus hirae, respectively. In the disinfectant evaluation, the extract achieved a logarithmic reduction of 3 to 4 cycles in the suspension test and 4 to 5 on stainless steel surfaces against Staphylococcus aureus and Enterococcus hirae, while sodium hypochlorite reached 7.47 logarithmic reductions. In conclusion, the ethanolic extract of Chamaesyce thymifolia has potential as a natural disinfectant for food-contact surfaces, although its efficacy is lower compared to sodium hypochlorite.